Kontribusi Produksi Cellular Lightweight Concrete Serat Limbah Pelepah Kelapa Ssawit Terhadap Emisi CO2 (Universitas Riau, 2019)
The vast palm oil plantations in Riau province which are 2,430,500 hectares (BPS Indonesia, 2017) have great potential as a provider of CPO (Crude Palm Oil) and other by-products and include waste. The midrib is always lowered along with the decrease in oil palm fruit bunches at harvest. Handling of waste from the midrib is only by stacking it in the field and letting it dry and self-destruct. Oil palm midribs are still a problem today because they can affect the global climate with greenhouse gas emissions. Carbon emissions can still be minimized by utilizing oil palm midribs. This study aims to measure the reduction of CO2 emissions as an added ingredient in the production of fiber CLC. Presentation of research results using descriptive methods. Research conducted in laboratories with an experimental approach is quantitative. The findings of this study are that the use of oil palm fronds as an added ingredient in producing CLC of solar and electric fuel fibers by 1 m3 can reduce CO2 emissions. The conclusion of this study is that CO2 emissions that can be reduced in the manufacture of 1 m3 of fiber CLC using diesel fuel is 111,582 tons/year and when using an electrically driven engine the CO2 emissions that can be reduced are 120.887 tons/year.